Human placenta‐derived mesenchymal stem cells inhibit apoptosis of granulosa cells induced by IRE1α pathway in autoimmune POF mice. (20th June 2019) - Li, Hongxing; Zhao, Wei; Wang, Li; Luo, Qianqian; Yin, Na; Lu, Xueyan; Hou, Yun; Cui, Jingjing; Zhang, Hongqin
Abstract: Previous studies have shown that the ovarian failure in autoimmune‐induced premature ovarian failure (POF) mice could be improved by the transplantation of human placenta‐derived mesenchymal stem cells (hPMSCs); however, the protective mechanism of hPMSCs transplantation on ovarian dysfunction remains unclear. Ovarian dysfunction is closely related to the apoptosis of granulosa cells (GCs). To determine the effects of hPMSCs transplantation on GCs apoptosis, an autoimmune POF mice model was established with zona pellucida glycoprotein 3 (ZP3) peptide. It is reported that the inositol‐requiring enzyme 1α (IRE1α) and its downstream molecules play a central role in the endoplasmic reticulum (ER) stress‐induced apoptosis pathway. So the aim of this study is to investigate whether hPMSCs transplantation attenuated GCs apoptosis via inhibiting ER stress IRE1α signaling pathway. The ovarian dysfunction, follicular dysplasia, and GCs apoptosis were observed in the POF mice. And the IRE1α pathway was activated in ovaries of POF mice, as demonstrated by, increased X‐box binding protein 1 (XBP1), up‐regulated 78 kDa glucose‐regulated protein (GRP78) and caspase‐12. Following transplantation of hPMSCs, the ovarian structure and function were significantly improved in POF mice. In addition, the GCs apoptosis was obviously attenuated and IRE1α pathway was significantly inhibited. Transplantation of hPMSCs suppressed GCs apoptosis‐induced by ER stress IRE1α signaling pathway in POF mice, which might contribute to the hPMSCs transplantation‐mediating ovarian function recovery.